Design of MOF based surface plasmon resonance sensors - Pan, Shanshan (2013)
Excited by lights, surface plasmons are electromagnetic waves propagating on the metal-dielectric interface. In a waveguide with a metal film, a surface plasmon mode can be coupled with a core-guided mode at a certain wavelength, signified by a sudden increase in losses. The fact that resonance wavelengths are sensitive to changes in the refractive index of the bordering analyte, lies the basis of surface plasmon resonance (SPR) sensors. Furthermore, when embedded into the microstructure of a fiber (MOF), the miniaturized SPR sensors support remote measurement. [1st Award]